WRITING COMPETITION SEBAGAI UPAYA MENCIPTAKAN KREATIVITAS MENULIS PADA MAHASISWA UNIVERSITAS JEMBER - Khusnun Nadhifah (Central Library of Universitas Sebelas Maret, 2018)
As a manifestation of the role of libraries in supporting Tri Dharma Perguruan Tinggi and efforts to create and develop creativity of writing students as a young generation, Jember University ofLibrary (UNEJ) conducted writing competition activities among universities throughout Jember Regency. The purpose of this paper is to provide information discourse (informative discourse) that through writing competition activities, can create and develop student creativity, especially UNEJ students through his paper. The method used is the study of case studies / case illustrated and closer to the descriptive study of the Writing Competition activities in the UNEJ Library, and supported by the lieratur and related data. Identify, analyze and investigate more deeply to study the object of research. Writing competition has created 176 student papers written in 49 scientific papers and 127 papers in short stories. Most participants were 151 or 85.80% came from UNEJ students especially students from the Faculty of Teacher Training and Education with the number of participants 63 students or 41.72%